Three genomes from the phylum Acidobacteria provide insight into the lifestyles of these microorganisms in soils - Ward, Naomi L.; Challacombe, Jean F.; Janssen, Peter H.; Henrissat, Bernard; Coutinho, Pedro M.; Wu, Martin; Xie, Gary; Haft, Daniel H.; Sait, Michelle; Badger, Jonathan; Barabote, Ravi D.; Bradley, Brent; et al. (Applied and environmental microbiologyApplied and environmental microbiology, 2009)
The complete genomes of three strains from the phylum Acidobacteria were compared. Phylogenetic analysis placed them as a unique phylum. They share genomic traits with members of the Proteobacteria, the Cyanobacteria, and the Fungi. The three strains appear to be versatile heterotrophs. Genomic and culture traits indicate the use of carbon sources that span simple sugars to more complex substrates such as hemicellulose, cellulose, and chitin. The genomes encode low-specificity major facilitator superfamily transporters and high-affinity ABC transporters for sugars, suggesting that they are best suited to low-nutrient conditions. They appear capable of nitrate and nitrite reduction but not N(2) fixation or denitrification. The genomes contained numerous genes that encode siderophore receptors, but no evidence of siderophore production was found, suggesting that they may obtain iron via interaction with other microorganisms. The presence of cellulose synthesis genes and a large class of novel high-molecular-weight excreted proteins suggests potential traits for desiccation resistance, biofilm formation, and/or contribution to soil structure. Polyketide synthase and macrolide glycosylation genes suggest the production of novel antimicrobial compounds. Genes that encode a variety of novel proteins were also identified. The abundance of acidobacteria in soils worldwide and the breadth of potential carbon use by the sequenced strains suggest significant and previously unrecognized contributions to the terrestrial carbon cycle. Combining our genomic evidence with available culture traits, we postulate that cells of these isolates are long-lived, divide slowly, exhibit slow metabolic rates under low-nutrient conditions, and are well equipped to tolerate fluctuations in soil hydration.
http://www.ncbi.nlm.nih.gov/pubmed/19201974?dopt=Abstract
Keywords: Anti-Bacterial Agents; bacteria; Biological Transport; Carbohydrate Metabolism; Cyanobacteria; DNA, Bacterial; Fungi; Genome, Bacterial; Macrolides; Molecular Sequence Data; Nitrogen; Phylogeny; Proteobacteria; Sequence Analysis, DNA; Sequence Homology; Soil Microbiology